2016
DOI: 10.5761/atcs.cr.16-00086
|View full text |Cite
|
Sign up to set email alerts
|

Lipoma-Like Bronchogenic Cyst in the Right Chest Sidewall: A Case Report and Literature Review

Abstract: Bronchogenic cyst most commonly occurs in the mediastinum, followed by the lung. We admitted a 59-year female patient with bronchogenic cyst being uniquely located on the right chest wall of the parietal pleura. Preoperative CT scan showed a local low-density lesion on the right chest wall. The lesion was removed by the thoracoscopic surgery. During the surgical resection, the lesion was observed to be located on the right chest wall. The lesion was surrounded by adipose tissue and covered with entire parietal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The typical pathological features of spinal bronchogenic cysts are pseudostratified ciliated columnar epithelium in the inner wall of the cysts, and in some cases cartilage and smooth muscle can be visible. [26] The reported cases as well as our present case all harbored these characteristics. Immunohistochemical staining can facilitate the diagnosis, which was positive to epithelial membrane antigen (EMA) but negative for glial fibrillary acidic protein (GFAP).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The typical pathological features of spinal bronchogenic cysts are pseudostratified ciliated columnar epithelium in the inner wall of the cysts, and in some cases cartilage and smooth muscle can be visible. [26] The reported cases as well as our present case all harbored these characteristics. Immunohistochemical staining can facilitate the diagnosis, which was positive to epithelial membrane antigen (EMA) but negative for glial fibrillary acidic protein (GFAP).…”
Section: Discussionsupporting
confidence: 73%
“…[29] Che et al also proposed that mediastinal bronchogenic cysts might have a risk of malignant transformation or spontaneous infection. [26] Chen et al reported spinal bronchogenic cysts might be associated with staphylococcus aureus infection or spontaneous hemorrhage. [2] In the current case and literature review, 9 (45%) cases received gross total resection and 11 (55%) cases received subtotal resection, and no recurrence was noted during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…In a typical noninfected cyst containing serous fluid, T1-weighted images show a low signal and T2-weighted images show a high signal, whereas cysts with increased protein content, hemorrhage, or mucosal components tend to show moderate to high T1-weighted signals on MRI. In cases where CT suggests a solid tumor, MRI becomes an essential diagnostic tool to make an almost precise preoperative diagnosis and differentiate between solid tumors and cysts by T1-weighted image signal showing moderate to high strength and T2-weighted image showing high signal strength [ 17 , 18 ]. Despite the value of various noninvasive diagnostic studies, a definitive diagnosis can only be made by surgical excision and tissue biopsy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis for bronchogenic cysts is established by their location in the body. A cystic neck mass might be an abscess, a thyroglossal duct cyst, or a bronchogenic cyst [25] . A cystic chest wall mass can be diagnosed as a dermoid cyst or teratoma, and a mediastinal cyst can be TB, foregut cyst, pericardial cyst, congenital cystic adenoid malformation, pulmonary sequestration, large B cell lymphoma, or enterogenic cyst [6] .…”
Section: Discussionmentioning
confidence: 99%